Oznaczanie palatalności l w drukach polskich z XVI wieku - Osiewicz, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article presents the results of an analysis of marking of palatal l in prints from the source database of Słownik polszczyzny XVI wieku (16th-century Polish language dictionary). The analysis takes into account the various conditions of this phenomenon: functional, frequency, contextual, textual, regional and publishing ones. The analysis shows that the rare records of the consonant l’ certified in the papers originated from the spelling of manuscripts. Most often, they appear in printed texts from the first half of the sixteenth century, mainly in the earliest texts and dictionaries, as well as in texts originating from southern Poland and southern Borderlands. Marking of palatal l in printed materials is characterised by a high degree of lexicalisation and dependence on the phonetic context and less dependent on the place of publication.